TEKNOLOGI PERANGKAT LUNAK PHOTOSHOP PORTABEL - AFIF, ZIHNIL; Adriyendi, Adriyendi (IAIN Batusangkar, 2011)
Photoshop is one of the standard image processing software professionals. Development of digital image manipulation influenced the creative industries, especially photography. To support the creative industries, especially photography, then the required professional standard image processing program that can run without being installed or are installed on the system. Such devices can be used by using media such as USB, MP3 or PDA. Usually packaged in a simple package and can be operated with just a few clicks away. How it works with the emulsion to the environment without touching the system registers. Therefore the system becomes more clear. When the software is connected to a computer, the application can be run directly without having to be installed first. Making a Photoshop Portable Photoshop Installer aim is that the software can be stored and run through an external storage media such as flash. Benefits of this Portable Photoshop is the user can carry data and programs required and can open it on another computer. Key words: Software, Photoshop Installer, Photoshop Portable